Social Support, Attachment Closeness, and Self-Esteem Affect Depression in International Students in China - Li, Yawen; Liang, Fei; Xu, Qiuyue; Gu, Simeng; Wang, Yansong; Li, Yang; Zeng, Zhi (Frontiers in Psychology, 2021)
ABSTRACT With the number of international students increases in China, the emotional problems of these students in China are also increasing. In order to explore the influencing factors of emotional problems in studying abroad, Social Support Rating Scale, Self-rating Depression Scale, Adult Attachment Scale and Self-Esteem Scale were used to survey 349 international students in China. The results showed that: (1)Attachment security has a significant direct predictive effect on depressions, (2)Social support plays a mediating role in the relationship between depression and attachment closeness, (3)Self-esteem regulates social support and affects depression through modulating attachment closeness. Therefore, improving the level of social support, attachment closeness, or self-esteem of international students in China can effectively reduce the depressions of international students.